Visceral Manipulation in Resources of Persian Medicine - Parva Namiranian; Mehrdad Karimi; Seyede Zahra Emami Razavi; Ahmad Fateh Garoos; Mohammad Hossein Ayati (Tehran University of Medical Sciences, 2021)
Persian Medicine applies various types of treatment, from changing lifestyle (known as Setteh-e-zarurieh) to using medicines and  manual interventions. Manual interventions have various types and indications in Persian Medicine. Visceral manipulation is one of them, which is defined as applying techniques to the viscera or the structures that support it in the case of disturbed motility or mobility related to a visceral system and the associated elements. Herein, Persian Medicine manuscripts were searched to find available information about visceral manipulation. There are many similarities between basic principles of visceral manipulation and Persian Medicine. Persian Medicine scholars have explained about anatomy of fascia and its components many years ago, which are very close to what today's knowledge is. Most probably, one of the very first scholars who has mentioned the idea of visceral manipulation is Avicenna (980-1037 CE). In his Canon of Medicine, Avicenna mentioned Ghamz as a treatment for liver injury. The available in vitro and animal studies support the positive effects of visceral manipulation. Persian Medicine scholars had detected nerve fibers and collagen which are fascia components. They are pioneer in this regard, too.